?Museality as a Matrix of the Production, Reception, and Circulation of Knowledge Concerning Religion - GRIESER, ALEXANDRA (My University, 2011)
Aesthetics of religion focuses on the sensual and representational aspects of religion and develops appropriate terminological tools. The idea of museality as an analytical and heuristic term for culture analysis is specified in the present paper by linking it to the history and dynamics of knowledge. Museums as institutions and cultural practice play a crucial role in the orders and politics of knowledge about religion in Europe. By means of different examples, museality is described as a specific and historically generated cultural pattern of perceiving, imagining, and knowing about religion in modernity. The examples focus on the production of different qualities of knowledge in exhibitions relating to religion, on transitions between religion and science in museums, and on popularisation as a mode of the circulation of knowledge about religion. These reflections on museality and knowledge dynamics could provide new potentials for inter-connective academic research, as well as for trans-disciplinary cooperation between the study of religion and museums.
PUBLISHED
Keywords: Religion; Aesthetics; Museum; Knowledge; Popularisation; Modernity; Aesthetics of Religion; Cultural history of religion; Religion and Theory; Religion, Modernity and Identity